Using a batch test to derive sorption data of fluoroquinolone antibiotics in humic acids - Fabregat-Palau, Joel; Rigol, Anna; Yu, Zhiqiang; Vidal, Miquel (MethodsX, 2023)
Fluoroquinolone antibiotics (FQs) are of concern due to their disrupting effects on environmental bacterial communities. Evaluating FQ sorption by soil components is important to understand their interaction with soils and to address their environmental (bio)availability. However, data in soil organic components, especially humic acids, are scarce. Batch experiments following OECD guidelines are suitable for testing the sorption of pollutants in solid matrices. Here, we applied this methodology, with specific changes in the experimental setup, to derive sorption data and to identify the factors affecting sorption of four common FQs in seven humic acids with contrasting properties. The effect of shaking time, pH, calcium concentration in solution and dissolved organic carbon (DOC) content on the quantification of the solid-liquid distribution coefficient (Kd) of norfloxacin in three reference humic acids was evaluated. Sorption reversibility and sorption analogy of four FQs were additionally assessed in these three reference materials, whereas the effect of initial norfloxacin concentration was evaluated in the overall set of seven humic acids. Sorption was fast, strong, non-linear, irreversible and affected by changes in the pH and calcium levels in solution. The bell-shaped sorption trend at varying pH values confirmed the key role of FQ speciation in sorption and the high Kd values indicated a positive effect of soil organic matter components on FQ sorption in bulk soils at environmentally relevant pH values.•Relevant factors affecting sorption of pollutants in environmental matrices must be considered to derive Kd values with low variability and high representativeness.•In this article we modify the experimental conditions of standard batch tests to identify the factors that affect the sorption of FQs in humic acids.•The methodological approach followed can be extrapolated to the evaluation of other combinations of pollutant and environmental matrix. [Display omitted]